Descriptive Analysis of Audit Effectiveness - Kharel, Shambhu Prasad (Academic Journal of Simara, 2026)
An internal audit system in commercial banks is to provide independent assurance to senior management and boards that operations align with policies, procedures, and effective risk management. This study identifies key organizational, professional, and structural factors influencing internal audit (IA) effectiveness in Nepalese commercial banks, assessing compliance with Institute of Internal Auditors (IIA) standards. In recent years, interest in internal auditing has grown significantly. This study examines factors affecting internal audit (IA) effectiveness organizational setting, independence, competence, management support, and audit committee existence in Nepalese commercial banks. A cross-sectional survey (n = 102 IA professionals; convenience sampling) used structured online questionnaires analyzed via SPSS v18. Descriptive results show high IA effectiveness (M = 4.81, 6-point Likert), with all variables ≥ 4.40 means. Findings affirm IIA standards compliance amid NRB Basel III/RBIA reforms, guiding banks to prioritize committees/independence for fraud prevention and governance. Implications aid practitioners/academics on IA determinants. These integrated measures prioritizing committees and independence will elevate IA from compliance to strategic governance, bolstering financial stability amid fraud risks and economic pressures, with NRB monitoring implementation for sector-wide resilience.